Measuring patient engagement: development and psychometric properties of the Patient Health Engagement (PHE) Scale - Graffigna, Guendalina; Barello, Serena; Bonanomi, Andrea; Lozza, Edoardo (Frontiers in Psychology, 2015)
Beyond the rhetorical call for increasing patients' engagement, policy makers recognize the urgency to have an evidence-based measure of patients' engagement and capture its effect when planning and implementing initiatives aimed at sustaining the engagement of consumers in their health. In this paper, authors describe the Patient Health Engagement Scale (PHE-scale), a measure of patient engagement that is grounded in rigorous conceptualization and appropriate psychometric methods. The scale was developed based on our previous conceptualization of patient engagement (the PHE-model). In particular, the items of the PHE-scale were developed based on the findings from the literature review and from interviews with chronic patients. Initial psychometric analysis was performed to pilot test a preliminary version of the items. The items were then refined and administered to a national sample of chronic patients (N = 382) to assess the measure's psychometric performance. A final phase of test-retest reliability was performed. The analysis showed that the PHE Scale has good psychometric properties with good correlation with concurrent measures and solid reliability. Having a valid and reliable measure to assess patient engagement is the first step in understanding patient engagement and its role in health care quality, outcomes, and cost containment. The PHE Scale shows a promising clinical relevance, indicating that it can be used to tailor intervention and assess changes after patient engagement interventions.